Clinical outcomes after immune checkpoint inhibitor-associated acute kidney injury: a cohort study - Vin-Cent Wu; Ting-Ya Yang; Min-Hsiang Chuang; Hong-Min Lin; Heng-Chih Pan; Yun Chou; Jui-Yi Chen (BMJ Open)
Objectives Immune checkpoint inhibitors (ICPi) have significantly improved survival for patients with advanced cancers. However, the occurrence of ICPi-associated acute kidney injury (AKI) and its clinical impact remains unclear. This study evaluates the effects of ICPi-associated AKI (ICPi-AKI) on mortality, kidney and cardiovascular outcomes in patients undergoing ICPi treatments.Design This multicentre retrospective cohort study with propensity score matching to balance baseline characteristics. The International Classification of Diseases, 10th Revision codes were used to identify individuals with cancer and treated with ICPi concurrently. Kaplan-Meier analyses coupled with log-rank tests were conducted to estimate the survival probabilities.Setting Data were sourced from the TriNetX database spanning records from 25 March 2011 to 5 April 2024.Participants Patients with cancer aged ≥18 years treated with ICPi with or without AKI occurrence.Primary and secondary outcome measures The primary outcome was all-cause mortality, and secondary outcomes included major adverse kidney events (MAKE), major adverse cardiovascular events (MACE), the composite of MAKE or MACE with death, and end-stage renal disease.Results The study identified 926 patients with cancer who developed ICPi-AKI (mean age, 67.1±11.8 years; 57.4% men). The control group consisted of 48 147 patients treated with ICPi but did not develop AKI (mean age, 65.3±13.1 years; 53.7% men). After matching, the ICPi-AKI group exhibited a higher risk of all-cause mortality (HR=1.27; 95% CI 1.02 to 1.61), MAKE (HR=3.83; 95% CI 1.72 to 8.40), MACE (HR=1.35; 95% CI 1.03 to 1.75)) compared with the non-ICPi-AKI group. Subgroup analyses confirmed these findings across various patient’s characteristics.Conclusion Individuals with ICPi-AKI are associated with an increased risk of all-cause mortality, MAKE and MACE. Enhancing awareness and timely intervention for ICPi-AKI are crucial for improving prognosis and reducing complications among patients with cancer.